The use of active methodologies and its impact on Chemistry teaching in Engineering courses: a case study of the UFC campus in Crateús (Research, Society and Development, 2022)
Active methodologies have been an innovative means of building student knowledge inside and outside the classroom. These include Problem-Based Learning, Cooperative Learning, and Inverted Classroom. Such methods were used in association with investigative methods for teaching Chemistry at the Federal University of Ceará Campus Crateús in a repeating class. From this, the effectiveness of this method in comparison to the traditional classroom methodology was analyzed. In addition to the continuous and formative assessments carried out with the students, opinion questionnaires applied by the teacher and monitor were used to obtain the research data. After applying the hybrid method, students were consulted and the following data were observed: 83.3% were satisfied with their learning, 93.3% said they had their doubts resolved and 60.0% indicated they were less pressured about the form of evaluation. There is also a reduction in the number of dropout students (4.9%) in the discipline when compared to traditional classes. Thus, it can be inferred that students have significant gains in conceptual understanding and skills addressed by the discipline of chemistry.